Konsep Wadiah Menurut Fikih dan KHES - Nikmah, Ckamilatun; Amalia Khoir, Firdausi; Noviandani, Hesty Ova (INAIFAS Press, 2022)
Jurisprudence is one of the fields of science in Islamic law that specifically discusses legal issues that regulate various aspects of human life, both personal life, society and human life with Allah, the Lord. In society, of course, humans are not far from economic problems. In the broad economic context, there is the term Wadi'ah which is also regulated in fiqh and KHES. Both fiqh and KHES have their own concept of wadi'ah. But it cannot be denied that KHES is a product of Indonesian fiqh thought in economic terms (muamalat). In the concept of wadiah fiqh, it is more detailed in explaining the legal bases, regarding the trust and safeguards. Also in the KHES concept, it is also explained in detail about the storage and maintenance of wadi'ah objects and other things. The point is that both of them can be used as procedures for conducting Wadi'ah contracts.